Personal Motivations and Systemic Incentives: Scientists on Questionable Research Practices - Bruton, Samuel V.; Medlin, Mary; Brown, Mitch; Sacco, Donald F. (Science and engineering ethics, 2020)
As concern over the use of questionable research practices (QRPs) in academic science has increased over the last couple of decades, some reforms have been implemented and many others have been debated and recommended. While many of these proposals have merit, efforts to improve scientific practices are more likely to succeed when they are responsive to the prevailing views and concerns of scientists themselves. To date, there have been few efforts to solicit wide-ranging input from researchers on the topic of needed reforms. This article is a qualitative report of responses from federally funded scientists to the question of what should be done to address the problem of QRPs in their disciplines. Overall, participants were concerned about how institutional and career-oriented incentives encourage the use of QRPs. Compared to previous recommendations, participants had surprisingly little confidence in the ability of ethics training to improve research integrity.